Colonization of two tropical forage grasses by Acromyrmex landolti (Hymenoptera: Formicidae) in Eastern Colombia - Lapointe, Stephen L.; Serrano, M.S.; Villegas, A (1993)
Established swards of the tropical forage grass Andropogon gayanus var. bis-quamulatus (Hochst.) Hack were heavily colonized by the leaf-cutter Acromyrmex landolti Forel over a period of 33 months in the eastern plains of Colombia. Density of Ac. landolti colonies in swards of A. gayanus increased from 23 @+ 9 at planting in 1988 to 263 @+ 57 colonies per 1800 m@^2 in 1991. Brachiaria humidicola (Rendle) Schweick was highly resistant to colonization by Ac. landolti. Colony density in swards of B. humidicola declined from 23 @+ 9 at planting in 1988 to 16 @+ 4 colonies per 1800 m@^2 in 1991. Mean density in adjacent savanna control plots varied over the three years from 114 @+ 23 to 225 @+ 24 colonies per 1800 m^2. Maps of colony entrances within swards were made yearly during 1989, 1990, and 1991. Comparison of maps demonstrated that colonies did not persist more than a single year at a given site implying colony migration. Excavation of over 100 colonies of Ac. landolti revealed a single entrance per colony in all cases.